從課程學理基礎與核心素養論K-12 年級課程綱要A Research on Curriculum Theoretical Foundations and Key Competencies of K-12 Curriculum Guideline in - 蔡清田Ching-Tien Tsai (Higher Education Foundation, 2011)
本研究結合了研究者近年主持的兩件整合型研究計畫初步成果，包括國家教育研究院所委託執行的「K-12中小學一貫課程綱要核心素養與各領域之連貫體系研究」與「中小學課程相關之課程、教學、認知發展等學理基礎與理論趨向」，這些研究旨在建立我國未來幼兒教育、初等教育、前期中等教育及後期中等教育的「K-12年級課程綱要」之課程發展學理基礎，預備下一波課程改革。本文從核心素養與課程學理的教育哲學、教學理論、認知心理學、文化研究與社會變遷等角度切入，分析課程發展相關學理基礎，並依據課程學理與核心素養研究，對我國「K-12年級課程綱要」的基本理念、課程目標、核心素養、學習領域及實施通則等提出建議，冀能提升我國國民核心素養。 The main goal of this research aims to build theoretical foundations of curriculum development in order to prepare for the next curriculum reform regarding the K-12 curriculum guideline in Taiwan. So far as theoretical foundations of curriculum development is concerned, this research focuses on the relationships between key competencies and curriculum theoretical foundations regarding with five theoretical dimensions - educational philosophy, teaching theory, cognitive psychology, cultural studies and social change. First, the researcher analyses key competencies and theoretical foundations of curriculum development according to the literature review of the related curriculum theories and related studies. Second, the researcher builds up a set of theoretical foundations regarding curriculum development which is suitable for Taiwanese historical and cultural contexts. Finally, according to the new set of curriculum theoretical foundations, the researcher makes some suggestions for the future K-12 curriculum guidelines in Taiwan.